Being Conscious of One’s Own Heroism: An Empirical Approach to Analyzing the Leadership Potential of Future CEOs - Pestana, Jose V.; Codina, Nuria (Frontiers in Psychology, 2019)
From the disciplinary field of the science of heroism, there is a need to deepen the processes that this science comprises and, at the same time, to test methods of inquiry to account for the variety of processes associated with this science. Linked to this sensitivity, the objective of this contribution is to jointly analyze, in a sample of future CEOs, what they imagine about heroism, their psychological types, and their values orientation. The sample consisted of 45 students (21 men and 24 women) between 22 and 47 years old (M = 26.69, SD = 4.47), who were part of a master's program oriented toward training future CEOs to be leaders. The analytical instruments were the Myers-Briggs Type Indicator (MBTI), a story that each participant developed about him/herself as the main hero or heroine, and a questionnaire on personal values. In the psychological types observed, the functions of thinking and sensing predominated, with intuition and feeling residing at a lower level of consciousness. With regard to the stories, the majority of the sample offered tales in which the hero/heroine was confronted with a mystery to solve (or mission to fulfil), faced difficulties, and, finally, achieved harmony between the personal and the collective. Regarding the values, significant associations are observed between the gender, the characteristics of the psychological types, and the content of the story about their own hero / heroine. In sum, the research carried out offers an empirical approach to the study of the subjective elements of heroism, combining quantitative and qualitative aspects in an educational setting, and broadening the perspectives on the science of heroism.